O método dos elementos finitos aplicado à análise de vigas e placas apoiadas em meio elástico - Figueiredo, Tânia Glacy do Brasil de (1974)
The Finite Element Method was applied to analyse beams and plates resting on soil considered as an isotropic, homogeneous and linear elastic medium. Some considerations about the actual behaviour of the soil and about the usual assumptions used to solve this and similar problems are discussed. The effects of eventual separation of contact surfaces are taken into account. A complete computer program for the calculation of rectangular plates and beams is presented. This program can also handle plates wich can be decomposed into rectangles.